2007
DOI: 10.1525/nr.2007.10.4.17
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Familial Experiences as Antecedents of Adult Membership in New Religious Movements: A Literature Review

Abstract: Is it possible to identify specific familial patterns as antecedents of adult membership in new religious movements? Can the choice of an NRM be predicted by the childhood experiences of individuals joining such movements? This international literature review seeks to answer these questions, investigating the assumption that early family experiences affect adults' decisions to join NRMs. It includes empirical studies that have been written in English, German and French since 1970, and gives an overview of find… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 12 publications
1
2
0
1
Order By: Relevance
“…Second, rather consistently across the different religious groups, in comparison to the general population, those who converted to mainstream religions were characterized by high levels of insecurity in attachment to their parents (especially to the father), high levels of avoidance in adult attachment, and a high need for cognitive order. This is consistent with previous research showing the role of affective and cognitive vulnerabilities favoring conversion, including conversion to new religious movements (Buxant et al, 2007;Granqvist & Kirkpatrick, in press;Murken & Namini, 2007). These results suggest the retention of classic psychological theories emphasizing the role of compensatory needs in partially explaining religious conversion.…”
Section: Conversion Motives 17supporting
confidence: 92%
“…Second, rather consistently across the different religious groups, in comparison to the general population, those who converted to mainstream religions were characterized by high levels of insecurity in attachment to their parents (especially to the father), high levels of avoidance in adult attachment, and a high need for cognitive order. This is consistent with previous research showing the role of affective and cognitive vulnerabilities favoring conversion, including conversion to new religious movements (Buxant et al, 2007;Granqvist & Kirkpatrick, in press;Murken & Namini, 2007). These results suggest the retention of classic psychological theories emphasizing the role of compensatory needs in partially explaining religious conversion.…”
Section: Conversion Motives 17supporting
confidence: 92%
“…Previous research has found a great deal of support for this affective-emotional compensatory function of religion (Granqvist & Kirkpatrick, 2008, for review). We thus hypothesised that ''freelance spiritual seekers'' would have an insecure attachment to parents in childhood, which has also been observed among New Age seekers (Farias & Granqvist, 2007;Granqvist & Hagekull, 2002;Granqvist, Ivarsson, Broberg, & Hagekull, 2007) and NRM members (Buxant et al, 2007;Murken & Namini, 2007). Concerning attachment to one's adult romantic partner, we hypothesised that ''free-lance spiritual seekers'' would also evidence insecurity in romantic attachment.…”
Section: Compensatory Motivesmentioning
confidence: 90%
“…insecure attachment) needs (Spilka, Hood, Hunsberger, & Gorsuch, 2003). Religion's compensation of previous cognitive and affective vulnerabilities seems also to be found among people who join NRMs (Aronoff, Lynn, & Malinoski, 2000;Murken & Namini, 2007;. The question thus arises as to whether defensive needs are also present among people attending the conferences on spiritual topics.…”
Section: Introductionmentioning
confidence: 99%
“…Rambo, 1993). Idee te zostały skonceptualizowane w paradygmacie [5] nawrócenia jako racjonalnego wyboru (Loveland, 2003), w którym opisuje się ( de-)konwertytę jako osobę dokonującą wyborów na "duchowym rynku" oraz w modelu dopasowania osoba-środowisko, w którym proces nawrócenia jest efektem interakcji między potrzebami, celami, cechami osoby a możliwościami ich realizacji, jakie oferuje konkretna grupa czy system religijny (Murken, Namini, 2007). Koncepcja dekonwersji Streiba jest zakorzeniona w zarysowanej wyżej tradycji badań nad nawróceniem.…”
Section: Nawrócenie (Konwersja) a Dekonwersjaunclassified